Web-based Library Development Using Codeigniter at SD Muhammadiyah 2 Waru - Ananta, Abdul Mu'iz Yuvan; Nurdyansyah (CV. Media Digital Publikasi Indonesia, 2024)
Based on (Law of the Republic of Indonesia No. 43 of 2007 concerning Libraries) it is stipulated that libraries are administrative institutions such as written, printed or recorded works that are professional and standardized systems that meet the needs of education, research, information, and preservation, and recreation of visitors (Chapter I Paragraph 1) In the law called